Current Burden of Hepatitis C Virus Infection Among Injecting Drug Users: A Mini Systematic Review of Prevalence Studies - Rafiq, Shafquat Mohammed; Banik, Gouri Rani; Khan, Sabina; Rashid, Harunor; Khandaker, Gulam (Infectious Disorders - Drug Targets, 2014)
Hepatitis C virus (HCV) infection among injecting drug users (IDUs) is a major public health concern. It is important to know the current burden of HCV infection among IDUs for targeted public health interventions in this high risk population. We systematically reviewed the published literature on prevalence of HCV infections among IDUs between January 1989 and April 2014. Sixty studies met the inclusion criteria for the review and subsequent analysis. Among the selected studies 26,311 IDUs were assessed for HCV infection of which 16,231 were positive, giving an overall prevalence of 61.7% (95% Confidence Interval [95% CI] 61.1-62.3%). Of the selected studies, 21 were from Asia, 20 from Europe, 13 from Americas, 5 from Australia and one from Africa. Combined regional estimates of HCV prevalence among IDUs showed that Africa has the highest mean prevalence of HCV among IDUs (97.3%, 95% CI 95.5-98.4%), however, this estimate was based only on one study from Mauritius. Europe has the second highest mean prevalence (65.9%, 95% CI 64.9-66.9%) followed by Australia (56.5%, 95% CI 53.8-59.2%). Our review suggests that the prevalence of HCV among IDUs is significantly high. There are very limited data from African nations. More comprehensive understanding of HCV epidemiology among IDUs including the risk behaviours are needed for this high risk group.
Keywords: intravenous drug user